(untitled) (Acta Polytechnica CTU Proceedings, 2017)
A modulus of elasticity was determined for eight differently foamed cement paste samples. Samples were loaded in the laboratory by a hydraulic press. The force acting on the sample was read directly from the laboratory press. Digital Image Correlation (DIC) analysis were used to draw deformations. Before loading pressure test was applied a random contrast pattern to the samples. Samples were captured by the camera in a one-second interval during the loading pressure test. The images were edited in the Adobe Photoshop Lightroom and then evaluated using Ncorr software. The result is a vertical and horizontal shift field. On the basis of the results obtained, it was possible to calculate the modulus of elasticity of each sample.